Elección de un filtro de carbón activado de cuesco de palma africana para agua pretratada (caso Del Llano S.A. Restrepo-Meta) (2021)
The present research work, whose objective was the choice of an activated carbon filter of African palm cuesco for pretreated water (case of Llano S.A. Restrepo-Meta), was carried out in order to complement the treatment of wastewater, the refinement of palm oil, To use it as boiler feed water, since Del Llano S.A. constantly implements changes in its productive processes to be a sustainable company. For this reason this work is part of exploratory research with a qualitative approach; the methodology was carried out in three phases that included activities incorporating the diagnosis of the current situation of wastewater treatment, with the help of collection techniques (interview) and analysis of the information, Bibliographic review and selection of activated carbon processing methodologies and filters based on this pollutant removal material, to achieve the required parameters (BOD, COD, SST, SSED, fats and oils and, pH).